Evaluation of screening for Chlamydia trachomatis among young women in primary health care services in Manaus, Amazonas State, Brazil - Dária Neves; Meritxell Sabidó; Camila Bôtto-Menezes; Nina Schwartz Benzaken; Lucília Jardim; Cynthia Ferreira; André Leturiondo; Camila Gurgel dos Santos; Adele Schwartz Benzaken
Abstract: Screening for Chlamydia trachomatis is not routinely offered to young asymptomatic women in Brazil. This study evaluated the performance, usefulness, and operational suitability of the Digene Hybrid Capture II (HCII) CT-ID DNA-test as an opportunistic screening tool to detect C. trachomatis in the public health system in Manaus, Amazonas State. Women aged 14-25 years who attended primary health care services were interviewed and one cervical specimen was collected during cytological screening. The HCII CT test was evaluated for its ability to detect the presence of C. trachomatis and against real-time PCR (q-PCR) in a subset of samples. Operational performance was assessed through interviews with providers and patients. Overall, 1,187 women were screened, and 1,169 had a HCII CT-ID test result (292 of these were also tested by q-PCR). Of those, 13.1% (n = 153) were positive. The sensitivity, specificity, positive and negative predictive values of HCII CT were 72.3% (95%CI: 65.4-78.6), 91.3% (95%CI: 84.1-95.9), 93.8% (95%CI: 88.5-97.1), and 64.4% (95%CI: 56.0-72.1), respectively. Sample collection caused discomfort in 19.7% of women. Among health professionals (n = 52), the main barriers reported included positive cases who did not return for results (56.4%), unwillingness to screen without an appointment (45.1%), and increase in their workload (38.8%). HCII CT-ID identified a high proportion of C. trachomatis cases among young women in Manaus. However, its moderate sensitivity limits its use as an opportunistic screening tool in primary health care settings in Manaus. Screening was well accepted although the barriers we identified, especially among health professionals, challenge screening detection and treatment efforts.